Trypanotolerant livestock in West and Central Africa. Volume 2. Country studies -Chapter 11. Togo - International Livestock Centre for Africa (International Livestock Centre for Africa, 1980)
Data on tsetse fly distribution, livestock population & distribution; and breed description, animal disease and productivity of Lagoon cattle, Borgu cattle, Sombra cattle, N'Dama cattle, sheep and goats. Note on herd composition and management and on research & development activities.